Corrigendum to “Therapeutic effect of ursolic acid in experimental visceral leishmaniasis” [Int. J. Parasitol. Drugs Drug Resist. 7 (2017) 1–11] (S2211320716300860) (10.1016/j.ijpddr.2016.12.002)) - Jesus, Jessica A.; Fragoso, Thais N.; Yamamoto, Eduardo S.; Laurenti, Marcia D.; Silva, Marcelo S.; Ferreira, Aurea F.; Lago, João Henrique G.; Santos-Gomes, Gabriela; Passero, Luiz Felipe D. [UNESP] (Elsevier, 2017)
In the original publication, the eighth author's surname was incorrect. The respective filiation is corrected as above. The authors would like to apologise for any inconvenience caused.